2023
DOI: 10.3390/plants12132523
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination Alters the Co-Decomposition of Leaves of the Invasive Tree Rhus typhina L. and the Native Tree Koelreuteria paniculata Laxm

Abstract: Invasive and native plants can coexist in the same habitat; however, the decomposition process may be altered by the mixing of invasive and native leaves. Heavy metal contamination may further alter the co-decomposition of both leaf types. This study evaluated the effects of two concentrations (35 mg·L−1 and 70 mg·L−1) and three types (Pb, Cu, and combined Pb + Cu) of heavy metal contamination on the co-decomposition of leaves of the invasive tree Rhus typhina L. and the native tree Koelreuteria paniculata Lax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 59 publications
1
3
2
Order By: Relevance
“…Thus, the four AIPs may not decompose more easily than those of P. laciniata. This phenomenon is not consistent with the current results, i.e., invasive plants decompose more easily than native plants [18,[51][52][53] or invasive plants decompose more slowly than native plants [54][55][56]. This finding in this study may be due to the similar proportion of soluble (easily decomposed) and recalcitrant (difficult to decompose) components in the leaves of the four AIPs and those of P. laciniata, i.e., the quality of the leaves of the four AIPs and those of P. laciniata was similar because the four AIPs and P. laciniata are Asteraceae species and these species have similar life cycles, life styles, and growing environments, and especially P. laciniata can often coexist with one or more of the four AIPs.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the four AIPs may not decompose more easily than those of P. laciniata. This phenomenon is not consistent with the current results, i.e., invasive plants decompose more easily than native plants [18,[51][52][53] or invasive plants decompose more slowly than native plants [54][55][56]. This finding in this study may be due to the similar proportion of soluble (easily decomposed) and recalcitrant (difficult to decompose) components in the leaves of the four AIPs and those of P. laciniata, i.e., the quality of the leaves of the four AIPs and those of P. laciniata was similar because the four AIPs and P. laciniata are Asteraceae species and these species have similar life cycles, life styles, and growing environments, and especially P. laciniata can often coexist with one or more of the four AIPs.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, R. typhina litter may decompose more effectively and rapidly than K. paniculate litter under urea. This finding is consistent with the previous studies, i.e., invasive plants decompose more easily and rapidly than native plants [18][19][20][21]. This phenomenon may be due to the higher percentage of soluble components and lower percentage of recalcitrant components in R. typhina litter compared to those of K. paniculate litter, and/or the compounds contained in R. typhina litter may be more readily released into the soil in the presence of urea.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, contrary to the first hypothesis, R. typhina litter did not degrade more easily than K. paniculata litter. These observations are also inconsistent with the results of previous research which has shown that invasive plants either degrade more rapidly [18][19][20][21], or significantly more slowly than native plants [58][59][60]. This phenomenon may be due to the similar proportions of soluble and recalcitrant components in the litter of the two trees [28].…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations